2019
DOI: 10.1111/tmi.13226
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Ebola psychosocial experiences and coping mechanisms among Ebola survivors: a systematic review

Abstract: objective A myriad of physical and psychosocial sequelae have been reported among Ebola survivors from previous Ebola virus disease (EVD) outbreaks, including the most recent in West Africa. This review examines the various forms of psychological distress experienced by EVD survivors, family and community reactions to EVD survivors and EVD survivors' coping mechanisms. methods We conducted a literature search of original articles employing Medline (Ovid), PubMed, Web of Science, Scopus, CINAHL, EBSCO host acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
145
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(161 citation statements)
references
References 66 publications
11
145
0
5
Order By: Relevance
“…For example, similar sequelae have been reported among HIV/AIDS patients in Hong Kong [52] and Uganda [53], in which HIV/ AIDS patients reported to feel less worthy of themselves, guilt, shame and self-blame for having HIV/AIDS. The common types of enacted stigma faced by EVD survivors in our study were social isolation, verbal abuse and fear of contagion, all of which are congruent with the common forms of stigma reported by EVD survivors in the wider literature [6]. These findings may be applicable to other emerging infectious disease survivors more generally, as similar forms of stigma from the public and healthcare staff have also been reported among SARS survivors in Hong Kong [54].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…For example, similar sequelae have been reported among HIV/AIDS patients in Hong Kong [52] and Uganda [53], in which HIV/ AIDS patients reported to feel less worthy of themselves, guilt, shame and self-blame for having HIV/AIDS. The common types of enacted stigma faced by EVD survivors in our study were social isolation, verbal abuse and fear of contagion, all of which are congruent with the common forms of stigma reported by EVD survivors in the wider literature [6]. These findings may be applicable to other emerging infectious disease survivors more generally, as similar forms of stigma from the public and healthcare staff have also been reported among SARS survivors in Hong Kong [54].…”
Section: Discussionsupporting
confidence: 85%
“…These include community long-term psychosocial counselling for EVD survivors to enhance their coping skills, community education and social support programs for EVD survivors, recruitment and training of trusted opinion leaders that can spread accurate de-stigmatising messages within communities, minimising social isolation and promoting economic empowerment of EVD survivors and EVD affected communities [44,57]. The mental health impact of surviving Ebola is enormous, and previous studies have reported that psychological distress, anxiety and depression are widespread among Ebola survivors [4,6]. Although the impact of Ebola -related stigma on mental illness among Ebola survivors is not well understood, stigma induced psychological distress and anxiety have been found to be associated with adverse mental health outcome among HIV/ AIDS patients [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to physical damage for patients, Widespread outbreaks of infectious disease, such as Ebola virus disease (EVD) and severe acute respiratory syndrome (SARS), was also associated with psychological distress and symptoms of mental illness [3,4]. Results from prospective studies consistently indicate psychological distress as a predictor for future health and disease outcomes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some survivors of EIDs are known to have suffered from mental health problems for years. Various forms of psychological distress were prevalent among Ebola survivors, including depression, anxiety, anger, grief, guilt, ashbacks, sadness, worthlessness, substance addiction, suicidal tendencies, and selfstigmatization [5]. The meta-analysis [13] indicated that in the post-illness stage of SARS and MERS, the point prevalence of PTSD was 32.2%, that of depression was 14.9%, and that of anxiety disorder was 14.8%.…”
Section: Introductionmentioning
confidence: 99%